CBIO-02. AMPLIFIED EGFR DRIVES TUMORIGENESIS IN TP53 WILD TYPE GLIOBLASTOMA THROUGH INHIBITION OF p53 FUNCTION BY DNA-PK/p53 BINDING. (6th November 2017) - Ding, Jie; Li, Xiaolong; Wasylishen, Amanda; Gao, Feng; Zhao, Yang; Baggerly, Keith; Lozano, Guillermina; Koul, Dimpy; Yung, W K Alfred
Abstract: Epidermal growth factor receptor (EGFR) amplification/mutation and TP53 mutation are two most frequent genetic events that differentiate molecular subtypes of Glioblastoma. An extensive analysis of the Glioblastoma TCGA database showed a near exclusivity between p53 mutation and EGFR amplification in two groups of patients with a third group that has neither event. To understand the relationship between EFGR amplification and TP53 status in tumorigenesis, we identified a series of glioma stem cell (GSC) lines with EGFR amplification from our GSC bank at MD Anderson Cancer Center. The EGFR amplified group was further divided into two groups based on p53 status: one group with wild type TP53 and the second group with mutant p53. To elucidate the role of EGFR in regulating p53 function in gliomas, we used CRISPR gene editing system to knock out EGFR expression in amplified cells lines. EGFR knockout clones were isolated only from TP53 mutant GSCs, but not in TP53 wild type GSCs. Knocking down of EGFR expression by siRNA, showed that p53 activity was increased in wild type TP53 GSCs as demonstrated by increased p21/WAF1/CDKN1A and BCL2 Associated X (BAX) expression. However, direct binding between EGFR and wild type p53 was not detected in these GSCs. Using co-IP and mass spectrometry, we found that DNA-PK is the linker between EGFR and wild type p53. EGFR knock down decreased the binding between DNA-PK and wild type p53. Furthermore, EGFR knock down resulted in decreased sphere numbers and sizes in wild type TP53 GSCs but not in mutant GSCs. In conclusion, we propose that EGFR functions as the driver of tumorigenesis and progression in EGFR amplified TP53 wild type GSCs by inhibiting wild type p53 function through DNA-PK, while EGFR amplification and TP53 mutation co-regulate the tumorigenesis process in TP53 mutant GSCs.